La dinámica participativa en las actas de reuniones del CONEI - Lilia Calderón Almerco (Pontificia Universidad Católica del Perú, 2012)
The dynamism of participation in the minutes of the CONEI meetings This is a discussion about the results of a documentary research about the participative dynamics into the minutes of the CONEI (Consejo Educativo Institucional) meetings of four public schools from Lima. The qualitative analysis of the minutes reveals that the participation characterizes for being formal, bureaucratic, unidirectional and conflicted; that is focused in the administrative and economic issues of the educational management. The discourse expresses an ideal vision about participation but negative about conflict. Also, the participation in the meeting is considered like being in the meeting, and the leadership of the principal and the teachers stands out, however, the students and parents are excluded or autoexcluded.